Use of a hydrological model for environmental management of the Usangu Wetlands, Tanzania - Kashaigili, Japhet J.; McCartney, Matthew P.; Mahoo, H.F.; Lankford, B.A.; Mbilinyi, B.P.; Yawson, Daniel K.; Tumbo, S.D. (International Water Management Institute, 2006)
This report presents the findings of a study to assess changes to flows into, and downstream of, the Usangu Wetlands, located in the headwaters of the Great Ruaha River, Tanzania. Hydrological data, in conjunction with remote sensing techniques, were used to provide insights into changes that have occurred to the Eastern Wetland. Results indicate that, between 1958 and 2004, inflows to the wetland declined by about 70 percent in the dry season months (July to November) as a consequence of increased human withdrawals, primarily for irrigation.